Coexistence of Tuberculosis and Mammary Carcinoma in a Goat. Issue 4 (30th May 2014) - Quintas, H; Alegria, N; Mendonça, A; Botelho, A; Alves, A; Pires, I
Contents: Synchronic occurrence of tuberculosis mastitis and mammary cancer is rare in humans and, to the best of our knowledge, not reported in domestic animals. Here, we present a case of a female adult goat of Serrana breed with simultaneous occurrence of a granulomatous mastitis, due to Mycobacterium caprae, and a mammary carcinoma. Both pathological conditions are rare in goats and should be included in differential diagnosis of mammary lesions.